The impact of customer service and perception towards TM Touch market share in the cellular telephone industry / Suhaili Mokhtar - Mokhtar, Suhaili (2002)
These project paper (MKT650) serve as the requirement for the completion of my Bachelor in Business Administration (Hons) Marketing program at University Technology Mara, Sarawak. The project paper entitles " The Impact of Customer Service and Perception toward TM Touch Market Share in The Cellular Telephone Market." The scope of the study will only cover Miri town. The study detailed out firstly, TM Touch customer service from the perspective of its people and processes that affects customer service and the improvement needed to upgrade the level of customer service. Secondly, is the perception of the customers on TM Touch image that is meant only for the urban subscribers and should it change or maintain its image in the market if it wants to gain a larger market share to compete with Maxis, Celcom, Digi and Time Cell. The study will recommend ways on how TM Touch can improve the level of customer service should the respondent states that it has a low level of customer service and should it change image and change the perception on how people perceive TM Touch.